A Case of Recurrent Pericardial Constriction Presenting with Severe Pulmonary Hypertension. (1st April 2013) - Brunner, Nathan W.; Ramachandran, Krithika; Kudelko, Kristina T.; Sung, Yon K.; Spiekerkoetter, Edda; Yang, Phillip C.; Zamanian, Roham T.; de Jesus Perez, Vinicio
Abstract : Chronic constrictive pericarditis (CP) is a relatively rare condition in which the pericardium becomes fibrotic and noncompliant, eventually resulting in heart failure due to impaired ventricular filling. The only curative treatment is pericardiectomy. Classically, CP does not usually cause severe pulmonary hypertension. When attempting to differentiate CP from restrictive cardiomyopathy, the presence of severely elevated pulmonary arterial pressure is used as a diagnostic criterion ruling against CP. We present a case of proven recurrent pericardial constriction following pericardiectomy presenting with severe pulmonary hypertension.